2012
DOI: 10.1210/jc.2012-1743
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Somatic Mutations in Parathyroid Tumors Using Whole-Exome Sequencing

Abstract: This study confirms the frequent role of the loss of heterozygosity of chromosome 11 and MEN1 gene alterations in sporadic parathyroid adenomas and implicates a previously unassociated methyltransferase gene, EZH2, in endocrine tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
123
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(137 citation statements)
references
References 43 publications
11
123
0
3
Order By: Relevance
“…Parathyroid adenomas, the most common cause of PHPT, are considered clonal proliferations of a transformed parathyroid cell that has acquired proliferative or survival advantage due to one of several genetic abnormalities including the PRAD1 translocation or mutations in the genes encoding menin, P53, and P27 (3)(4)(5)(6)(7). Regardless of type, most authors consider parathyroid tumors clonal (8,9) although intratumoral heterogeneity has been observed and polyclonality of microdissected parathyroid adenomas has been reported (10,11).…”
mentioning
confidence: 99%
“…Parathyroid adenomas, the most common cause of PHPT, are considered clonal proliferations of a transformed parathyroid cell that has acquired proliferative or survival advantage due to one of several genetic abnormalities including the PRAD1 translocation or mutations in the genes encoding menin, P53, and P27 (3)(4)(5)(6)(7). Regardless of type, most authors consider parathyroid tumors clonal (8,9) although intratumoral heterogeneity has been observed and polyclonality of microdissected parathyroid adenomas has been reported (10,11).…”
mentioning
confidence: 99%
“…However, these derangements occur, collectively, in a minority of these tumors [2,3,7], and even when present are likely to cooperate with other driver lesions; thus multiple additional targets for tumorigenic mutation and future therapeutics undoubtedly exist. Indeed, studies of the genomes of parathyroid adenomas using a variety of methods have revealed a complex and heterogeneous landscape of chromosomal and DNA sequence level changes [8][9][10][11][12][13]. Identification of novel, recurrently altered genes has been difficult due to a low frequency of mutation observed in candidate genes and the limited number of cases examined [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies of the genomes of parathyroid adenomas using a variety of methods have revealed a complex and heterogeneous landscape of chromosomal and DNA sequence level changes [8][9][10][11][12][13]. Identification of novel, recurrently altered genes has been difficult due to a low frequency of mutation observed in candidate genes and the limited number of cases examined [8,9]. For example, EZH2 mutation was observed in 1 of 8 adenoma exomes, and overall in 2/193 adenomas after direct sequencing of additional samples [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, genetic evidence argues against such a progression for parathyroid carcinoma. Genomic and genetic alterations common in benign parathyroid adenomas, most prominently loss of chromosome 11q and accompanying mutation of MEN1, which occur in 35% of parathyroid adenomas [2][3][4][5][6][7][8] , are rarely, if ever, seen in parathyroid cancer [3,4,8,9] . The clearly distinguishable patterns of genomic and genetic alterations present in parathyroid adenomas versus carcinomas suggests that parathyroid cancer most commonly arises de novo, rather than evolving from a preexisting benign adenoma [8] .…”
Section: Genetic Alterations In Parathyroid Cancermentioning
confidence: 99%